Pastoral lessons from Augustine"s theological correspondence with women - Smither, Edward (HTS teologiese studies, 2016)
Augustine of Hippo (354–430) was a fourth- and fifth-century monk-bishop who left a great imprint on the spiritual leaders of his day by overseeing the monastery at Hippo Regius and also authoring a significant corpus of letters that were pastoral in nature. What is often overlooked in the study of his pastoral ministry and, thus, the focus of this article, is Augustine’s theological correspondence with 15 different women. Through surveying the themes and issues in these letters, I have endeavoured to show that, though a monk, Augustine did care for women in his pastoral ministry and his letters show that he discussed with women many of the issues of his day (pastoral issues, church matters, monastic ideas, theology, and practical theology) that he also discussed with his male correspondents. In short, Augustine believed that these women were much like his mother Monica – capable of grasping biblical and theological issues – and he valued them as an important part of the church. I conclude the article by summarising Augustine’s approaches to and values for ministering to women.